Contribuições para regulamentação da tecnologia PLC no Brasil com base em testes de campo - MARQUES, Fabio da Silva (2009)
This work describes the data transmission technology called PLC (Power Line Communications) that demanded discussions in order to assess the potential for interference in services currently in operation and using radio frequency in the range of 1,705MHz to 30MHz The equipment used in this type of technology, and its principle of operation principle based on the field trials in indoor and outdoor environments are described. It is presented in this paper a case study about the influence caused in carrying on a network PLC because of electromagnetic interference. It was possible determining the noise influence from electricelectronic equipment in the performance of a network PLC and what types of equipment are more harmful to the communication. Finally some suggestions are pointing, as the use of mitigation techniques which technology has greatest potential for success by contributing to the regulation and standardization in Brazil